Surgical site infections following oral cavity cancer resection and reconstruction is a risk factor for plate exposure - Christopher M. Yao; Hedyeh Ziai; Gordon Tsang; Andrea Copeland; Dale Brown; Jonathan C. Irish; Ralph W. Gilbert; David P. Goldstein; Patrick J. Gullane; John R. de Almeida (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Plate-related complications following head and neck cancer ablation and reconstruction remains a challenging problem often requiring further management and reconstructive surgeries. We aim to identify an association between surgical site infections (SSI) and plate exposure. Methods A retrospective study between 1997 and 2014 was performed to study the association between postoperative SSI and plate exposures. Eligible patients included those with a history of oral squamous cell carcinoma who underwent surgical resection, neck dissection, and free tissue reconstruction. Demographic and treatment related information was collected. SSI were classified based on CDC definition and previously published literature. Univariable analysis on demographic factors, smoking history, diabetes, radiation, surgical and hardware related factors; while multivariable analysis on SSI, plate height, segmental mandibulectomy defects and radiation were conducted such as using cox proportional hazard models. Results Three hundred sixty-five patients were identified and included in our study. The mean age of the study group was 59.2 (+/−13.8), with a predominance of male patients (61.9%). 10.7% of our patient cohort had diabetes, and another 63.8% had post-operative radiation therapy. Patients with SSI were more likely to have plate exposure (25 vs. 6.4%, p <0.001). Post-operative SSI, mandibulectomy defects, and plate profile/thickness were associated with plate exposure on univariable analysis (OR = 5.72, p < 0.001; OR = 2.56, p = 0.014; OR = 1.44, p = 0.003 respectively) and multivariable analysis (OR = 5.13, p < 0.001; OR = 1.36, p = 0.017; OR = 2.58, p = 0.02 respectively). Conclusion Surgical site infections are associated with higher rates of plate exposure. Plate exposure may require multiple procedures to manage and occasionally free flap reconstruction.